(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2025)
Rheumatic heart disease continues to pose a considerable public health challenge globally, impacting approximately 40 million individuals, as reported by the World Health Organization. Present study intended to measure the spectrum of valvular lesions in patients with rheumatic heart disease (RHD) using echocardiography among a South Indian Cohort. A total of 216 patients from Dhanya Cardiac Center, Salem, South india were enrolled, with a mean age of 43.7 years and a median age of 43 years. The majority of patients (64.4%) were between 31 and 60 years old, and 61.6% were female. Nearly all patients (92.6%) had a history of rheumatic fever. Valvular stenosis was observed in 92.6% of the patients, with mitral stenosis being the predominant type at 90.3%, followed by aortic stenosis (10.2%) and tricuspid stenosis (0.5%). Additionally, 99.1% of patients exhibited valvular regurgitation, predominantly mitral regurgitation (97.2%), with aortic regurgitation seen in 72.7%. The severity of mitral regurgitation ranged from mild (60.6%) to severe (5.1%), while 42.1% of patients had mild aortic regurgitation. These findings underscore the significant burden of mitral valve involvement in RHD and highlight the need for targeted interventions in this population. The study adds to the understanding of regional variations in RHD presentation and suggests avenues for future research focused on optimizing diagnostic and therapeutic approaches.